Flexible building services of office-based environments : principles for designers. (CIBSE ;, 2000)
This TM provides guidance for building services engineers and other professionals on the design of building services in office environments where frequent changes of activity and layout are expected to occur, to assist the design of more flexible building services for office-based environments. In a rapidly changing business environment, clients want buildings that can support and change with business needs. They increasingly seek premises that can more readily adapt to their needs. --